The development and function of vertebrate cilia - Roy, Sudipto (Henry Stewart Talks, 2010)
Motile and primary cilia, Developmental regulation of ciliogenesis, Role of the Roxj1 transcription factor in motile cilia formation, Hedgehog signaling and primary cilia, DZIP1 proteins in ciliary biogenesis